2019
DOI: 10.3174/ajnr.a6081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Explicitly Stated Interval Change on Noncontrast Head CT Radiology Reports

Abstract: BACKGROUND AND PURPOSE: Consistent and standardized reporting of interval change for certain diagnoses may improve the clinical utility of radiology reports. The purpose of this study was to assess explicitly stated interval change of various findings in noncontrast head CT reports. MATERIALS AND METHODS: A retrospective review was performed on successive noncontrast head CT radiology reports from the first 2 weeks of January 2014. Reports with at least 1 prior comparison CT scan were included. Reports with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…28 Authors of this study suggested the use of structured radiology reports to improve interval change reporting on follow-up exams. 28 Such use of structured reporting has been endorsed to improve clarity and consistency of reporting between radiologists. [24][25][26]29 Standardized templates have been widely distributed through online resources, such as RadReports from the Radiological Society of North America (RSNA), the foundation of which is based upon RadLex online indexing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Authors of this study suggested the use of structured radiology reports to improve interval change reporting on follow-up exams. 28 Such use of structured reporting has been endorsed to improve clarity and consistency of reporting between radiologists. [24][25][26]29 Standardized templates have been widely distributed through online resources, such as RadReports from the Radiological Society of North America (RSNA), the foundation of which is based upon RadLex online indexing.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of change assessment in our study (32% of reports) was similar to a recent retrospective review of 230 successive follow-up CT exams, which demonstrated absent interval change evaluation in approximately 33% of reports. 28 Authors of this study suggested the use of structured radiology reports to improve interval change reporting on follow-up exams. 28 Such use of structured reporting has been endorsed to improve clarity and consistency of reporting between radiologists.…”
Section: Discussionmentioning
confidence: 99%